PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SISWA SD NEGERI KEDAWUNG 4 SRAGEN TAHUN PELAJARAN 2022/2023 - Zunaedah, Ummi Afifi; Mahmud, Amir (Universitas Nahdlatul Ulama Surakarta, 2024)
Islamic education serves to instill three elements that are interrelated in students: faith, science, and charity. Therefore, both in terms of theory and application, the condition/characteristics of a teacher greatly determine the level of mastery of the student on the concept of Islamic Religious Education. This article aims to find out if there is an influence of learning motivation on learning achievement of Islamic Religion Education and Budi Pekerti students of grade V SD State Kedawung 4 Sragen Year of Education 2022/2023. The type of research used in this research is quantitative. The results of the study showed that there was an influence between the variable X (Learning Motivation) on the Variable Y (Islamic Education Learning Performance and Budi Pekerti) based on the result value (r_xy) of the product moment greater than (r table) is 0.784 > 0.374 at 95 % significance at N= 28. And at 99% significance is 0.078 > 0.478 at N=28, so the hypothesis is accepted.